2017
DOI: 10.1249/mss.0000000000001071
|View full text |Cite
|
Sign up to set email alerts
|

Adaptations with Intermittent Exercise Training in Post- and Premenopausal Women

Abstract: Twelve weeks of intermittent exercise training increased BMD, intermittent exercise capacity, and V˙O2max in PM and PRM, with PM also having positive changes in body composition. Additional 40 wk of training with a reduced frequency was sufficient to preserve these physiological adaptations and also improve blood glucose regulation in PM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
1
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 34 publications
4
16
1
3
Order By: Relevance
“…Computation of YYIE1 test global means, SDs and quantiles (Figure 5) involved 12 studies/subgroups reporting on 770 participants (median age = 21.3 years, IQR = 18.8–44.3 years) (Metaxas et al, 2005; Castagna et al, 2006a; Lategan et al, 2011; Rowan et al, 2012; Deliceoglu, 2013; Mohr et al, 2014; Akashi et al, 2015; Fløtum et al, 2016; Julian et al, 2017; Krustrup et al, 2017; Seidelin et al, 2017). …”
Section: Resultsmentioning
confidence: 99%
“…Computation of YYIE1 test global means, SDs and quantiles (Figure 5) involved 12 studies/subgroups reporting on 770 participants (median age = 21.3 years, IQR = 18.8–44.3 years) (Metaxas et al, 2005; Castagna et al, 2006a; Lategan et al, 2011; Rowan et al, 2012; Deliceoglu, 2013; Mohr et al, 2014; Akashi et al, 2015; Fløtum et al, 2016; Julian et al, 2017; Krustrup et al, 2017; Seidelin et al, 2017). …”
Section: Resultsmentioning
confidence: 99%
“…; Seidelin et al . ). Here we propose that greater improvements in vascular function may be achieved in women if training is initiated in middle age, soon after menopause, as opposed to many years (5–10 years) after menopause.…”
Section: Introductionmentioning
confidence: 97%
“…Regular exercise training is clearly beneficial for men at all ages and numerous studies have shown that men up to very old age profit from training in terms of vascular and cardiac function (Schmidt et al 2014;Vorup et al 2017). In women at older age, however, there are limited and conflicting data on a positive effect of exercise training on cardiac (Spina et al 1993;Egelund et al 2017) and vascular function (Pierce et al 2011a;Moreau et al 2013;Nyberg et al 2016;Seidelin et al 2017). Here we propose that greater improvements in vascular function may be achieved in women if training is initiated in middle age, soon after menopause, as opposed to many years (5-10 years) after menopause.…”
Section: Introductionmentioning
confidence: 99%
“…,b) and skeletal muscle performance (Seidelin et al . ) than low to moderate intensity training (Pierce et al . ; Moreau et al .…”
Section: Introductionmentioning
confidence: 99%